Subcortical Network Properties in Parkinson's Disease - Hesse, Jared Grant (Wake Forest University, 2016)
Parkinson’s disease has been characterized as a “disconnection syndrome” reflecting the disruption of neural pathways. Network science analyses provide a promising way of further analyzing this characterization given the rich data they provide about the interrelationships between brain areas. In this study, network science graph theory based analyses were performed using the resting state data from 14 individuals with Parkinson’s disease.
Keywords: fMRI; Functional connectivity; Network; Parkinson's; Parkinson's disease; Subcortical